2017
DOI: 10.1080/19397038.2017.1348562
|View full text |Cite
|
Sign up to set email alerts
|

Designing individualisation of eco information: a conceptual framework and design toolkit

Abstract: Eco labelling is the practice of eco information provision that most directly addresses consumer behaviour. Nowadays consumers are facing difficulties in perceiving and understanding existing eco labels. In previous work we proposed the conceptual framework of eco information individualisation which tailors eco labels according to the specific needs of individual users using contextual technologies. This paper extends the conceptual framework by introducing a more structured way of considering the personal dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…Indeed, a similar approach has been used in other studies investigating sustainable labels [17,18,31]. Furthermore, qualitative approaches have been widely used to study user/experience-centered designs [32][33][34]. In such research contexts, focus groups are particularly recommended [18].…”
Section: Design and Data Collectionmentioning
confidence: 99%
“…Indeed, a similar approach has been used in other studies investigating sustainable labels [17,18,31]. Furthermore, qualitative approaches have been widely used to study user/experience-centered designs [32][33][34]. In such research contexts, focus groups are particularly recommended [18].…”
Section: Design and Data Collectionmentioning
confidence: 99%
“…Faludi [35] tested three sustainable design methods with over 500 professionals and students to find that they valued parts, but not all, of each method, suggesting great room for improvement and cross-fertilization of SDMTs. Kwok and Hallstedt [36] found that inadequate communication between design teams and consumers cause product developers to inadequately understand consumer needs, and cause consumer confusion about product sustainability and the complexity thereof [37].…”
Section: Rq1: What Are the Needs And Values Of Industry Regarding Susmentioning
confidence: 99%
“…Communicate sustainability information to customers and users, to demonstrate the value of the sustainability strategies or accomplishments embodied in the product [36,37,69].…”
mentioning
confidence: 99%
“…Table 1 presents the dimensions, factors, and interrelations (between dimensions). Such detailed frameworks are complex to use in design practice, as reported by other researchers [10,12,15,24,25]. Additionally, there is uncertainty applying such frameworks for educational game design in practice [8][9][10][11]14].…”
Section: The League Frameworkmentioning
confidence: 99%
“…Card-based tools have previously been used by researchers to put together knowledge from diverse areas (such as tangible interfaces, IoT, playfulness, and eco information) into an easily accessible form to stimulate design thinking and aid in design practice [7,24,26,28]. Many researchers focused on game design or gamification.…”
Section: Card-based Tools In Various Domainsmentioning
confidence: 99%